Conditioned Place Preference Induced by Licit Drugs: Establishment, Extinction, and Reinstatement - Yu Liu; Bernard Le Foll; Yanli Liu; Xi Wang; Lin Lu (The Scientific World Journal)
The conditioned place preference (CPP) model has been widely used to evaluate the rewarding effects of abused drugs, and recently, the extinction and reinstatement phases of this paradigm have been used to assess relapse to drug seeking. The vast majority of studies have focused on CPP induced by illicit drugs, such as psychostimulants and opioids. Although legal psychoactive drugs, such as ethanol, nicotine, and caffeine, are more widely used than illegal drugs, the establishment, extinction, and reinstatement of CPP produced by these licit drugs are less well understood. The present review discusses the extant research on CPP induced by legal drugs. We first describe the CPP model and discuss the behavioral procedures used to induce CPP for ethanol, nicotine, and caffeine. We then summarize the neuronal substrates that underlie CPP induced by these drugs from a genetic perspective. Finally, we draw on findings from pharmacological studies and discuss the neurotransmitters and neurohormones underlying CPP produced by ethanol, nicotine, and caffeine.